The roles, prospects and challenges of academic lawyers in legal education in Nigeria (2009)
Legal education is the education of individuals who intend to become legal professionals or those who simply intend to use law degree to achieve some end related to law (such as politics or academic) or business. The qualification includes a first degree in law, which may be studied at either undergraduate or graduate level depending on the country and vocational courses which prospective lawyers are required to pass in some countries before they can enter practice. Legal education also encompasses higher degree such as doctorate for more advanced academic study. This paper, therefore, examined the roles, prospects and challenges confronting academic lawyers in the pursuit of legal education in Nigeria. In order to ensure necessary elaboration, reference has been made to other countries that operate similar legal education with Nigeria.